1982
DOI: 10.1093/nar/10.24.8049
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 hyperacetylation and rapid turnover of its acetyl groups in transcriptionally inactive rooster testis spermatids

Abstract: In order to study the relationship between acetylation of histones, chromatin structure and gene activity, the distribution and turnover of acetyl groups among nucleosomal core histones and the extent of histone H4 acetylation were examined in rooster testis cell nuclei at different stages of spermatogenesis. Histone H4 was the predominant acetylated histone in mature testes. Hyperacetylation of H4 and rapid turnover of its acetyl groups are not univocally correlated with transcriptional activity since they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 14 publications
0
55
0
3
Order By: Relevance
“…However these data represent only circumstantial evidence and there are several recent reports, which do not favor this concept; e.g. in rat liver nuclei transcribing chromatin was not enriched with acetylated histones (36); in Drosophila embryos no correlation between histone acetylation and transcription could be established (37); during spermatogenesis H4 (hyper)acetylation obviously serves other purposes than transcriptional activity as demonstrated in rooster (38) as well as in trout (39). Results with the SV-40 minichromosome (40) and with HTC-cells (41) also cast doubt on the theory of acetylation-transcription coupling.…”
Section: Discussionmentioning
confidence: 76%
“…However these data represent only circumstantial evidence and there are several recent reports, which do not favor this concept; e.g. in rat liver nuclei transcribing chromatin was not enriched with acetylated histones (36); in Drosophila embryos no correlation between histone acetylation and transcription could be established (37); during spermatogenesis H4 (hyper)acetylation obviously serves other purposes than transcriptional activity as demonstrated in rooster (38) as well as in trout (39). Results with the SV-40 minichromosome (40) and with HTC-cells (41) also cast doubt on the theory of acetylation-transcription coupling.…”
Section: Discussionmentioning
confidence: 76%
“…Among nuclear proteins identified, one surprise has been the identification of RuvB-like 1 protein known to have ATPase and DNA helicase activities and to be part of the NuA4 histone acetyltransferase complex. Extensive histone hyperacetylation is known to take place during the nucleo- histone to nucleoprotamine transition in spermatogenesis [44,45]. Also, upon fertilization, a new wave of histone hyperacetylation takes place concomitant to the paternal nucleosome formation.…”
Section: Resultsmentioning
confidence: 99%
“…At fertilization, the mature sperm cells are packaged densely with protamines, whereas maternal genome is packaged with histones. Subsequently, upon fertilization, the highly compact nucleoprotamine structure must be unpacked and reorganized into a nucleosomal structure [165]. Recent studies have shown that some epigenetic errors in these processes are a possible cause of male infertility.…”
Section: Epigenetic Modifications and Male Infertilitymentioning
confidence: 99%